1972
DOI: 10.4039/ent1041963-12
|View full text |Cite
|
Sign up to set email alerts
|

PHEROMONE EFFECTS OF CIS-9 LONG CHAIN ALKENES ON THE COMMON HOUSE FLY — AN IMPROVED SEX ATTRACT ANT COMBINATION

Abstract: Can. Enr. 104: 1963-1965 (1972) The effects on the house fly, Musca dornestica (L.), of a series of cis-9 alkenes containing 19-25 carbon atoms were investigated. An unexpectedly wide spectrum of these homologous hydrocarbons showed biological activity. Synergism and interesting changes in behavioural responses (excitement, mating, and orientation) varying with structure and concentration were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

1974
1974
2004
2004

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 3 publications
0
9
1
Order By: Relevance
“…The reduction in flight activity produces a concomitant decrease in the probability of individual flies entering the visual field of the clustered pseudoflies. Laboratory studies have demonstrated that ( Z )‐9‐tricosene induces increased activity levels ( Mansingh et al . 1972 ; Nicholas 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction in flight activity produces a concomitant decrease in the probability of individual flies entering the visual field of the clustered pseudoflies. Laboratory studies have demonstrated that ( Z )‐9‐tricosene induces increased activity levels ( Mansingh et al . 1972 ; Nicholas 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory investigations have consistently demonstrated that ( Z )‐9‐tricosene elicits increased activity, orientation and short‐range attraction of male M. domestica to the odour source ( Carlson et al . 1971 ; Mansingh et al . 1972 ; Rogoff et al .…”
Section: Introductionmentioning
confidence: 99%
“…(i) Larger targets attract more flies, (ii) ( Z )‐9‐tricosene attracts mainly male flies, and (iii) higher concentrations of ( Z )‐9‐tricosene increase the catch. (Z)‐9‐tricosene is present in the cuticular hydrocarbons of female houseflies, and has long been known to attract as a short‐range attractant and copulatory stimulant for males ( Rogoff et al., 1964; Mayer and James , 1971; Mansingh et al., 1972; Carlson et al., 1974; Richter et al., 1976). In field trials in poultry houses it also increases the catch of females ( Mitchell et al., 1975; Chapman et al., 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…This questions the role (Z)-9-tricosene may actually play in mating behaviour. (Z)-9-tricosene enhances sexual activity in male houseflies (Mansingh et al,1972;Uebel et al, 1976;Adams & Holt, 1987;La-France et al 1989;Lemke et al,1990;Islam & Port, 1994) which may explain its relatively high production by the females in the laboratory where environmental conditions are constant and not extreme and where selection pressure is high. However, our results suggest that it is not decisive for mating.…”
Section: Discussionmentioning
confidence: 99%